Pengaruh Strategi Marketing Mix terhadap Pendapatan Pedagang Kaki Lima Kuliner Kota Bukittinggi dengan Digital Marketing sebagai Variabel Moderasi - Nanda, Irvan; Izmuddin, Iiz (Lembaga Yasin AlSys, 2024)
The purpose of this study was to analyze the effect of the marketing mix strategy on street vendors' income at culinary street vendors in the city of Bukittinggi and estimate digital marketing to moderate the effect of marketing mix strategies on street vendors' income at culinary street vendors in the city of Bukittinggi). The research method uses a quantitative approach (correlation research). The research location in the city of Bukittinggi will be carried out in 2023 until completion. Data was obtained using a questionnaire which was distributed to 30 respondents to all street vendors. The data analysis used in this study is the Warp Partial Least Square program. With the help of Warp-PLS software 5. The results of the MIX Marketing Strategy research have a positive and significant effect on the income of street vendors with a β value of 0.65 and a P-Value of 0.01, smaller than 0.5 indicated by an R^2 value of 0.42, which means that the contribution to the influence of Marketing Strategy MIX to street vendors income by 42%. Digital Marketing has a positive and significant effect on PKL's income with a β value of 0.68 and a P-Value of 0.01, small of 0.5 indicated by an R^2 value of 0.46, which means that the contribution of Digital Marketing's influence on Street vendors' income is 46%. Digital Marketing moderates the effect of the MIX Marketing Strategy on street vendors' income with a moderation effect coefficient of 0.16 and a P-Value of 0.02, less than 0.05. indicated by the R^2 value of 0.44 (44%).